Determination of Sex from Hand Dimensions: A Study in an Ethnic Population from Eastern India - Shreyasi Roy (Light House Polyclinic Mangalore, 2021)
Theoretical development of the inter-relationship between sex determination and hand dimensions is important in the identification of mutilated and skeletal remains found in several mass disasters and fatal assault cases. The primary aim of the study was to determine sex from hand dimensions (HL: hand length and HB: hand breadth) of adult Rajbanshi individuals. Data for the present study were obtained from 400 (200 males; 200 females) unrelated adult (aged 20-60 years) Rajbanshi individuals. The data was statistically analyzed using statistical tests such as descriptive statistics, one-way analysis of variance (ANOVA) and two-way ANOVA. Binary Logistic Regression was employed to develop predictive sex models. We found that the mean values of HL and HB of both hands were higher in males compared to females. Statistically significant sex differences were found in hand lengths only. Bilateral differences in HL and HB were found to be statistically significant in both sexes. Predictive sex models were found to be significant (p<0.05) and bear reliable accuracies for both sexes separately as well as combinedly. It could be inferred that hand dimensions can identify sex with reasonable accuracy. However, hand length appeared to be the most reliable sex discriminator.